Adolescent self‐harm prevention and intervention in secondary schools: a survey of staff in England and Wales. Issue 3 (5th December 2018) - Evans, Rhiannon; Parker, Rachel; Russell, Abigail Emma; Mathews, Frances; Ford, Tamsin; Hewitt, Gillian; Scourfield, Jonathan; Janssens, Astrid
Abstract : Background: Adolescent self‐harm is a major public health concern. To date there is a limited evidence‐base for prevention or intervention, particularly within the school setting. To develop effective approaches, it is important to first understand the school context, including existing provision, barriers to implementation, and the acceptability of different approaches. Methods: A convenience sample of 222 secondary schools in England and Wales were invited to participate in a survey, with a 68.9% ( n  = 153) response rate. One member of staff completed the survey on behalf of each school. Participants responded to questions on the existing provision of adolescent self‐harm prevention and intervention, barriers to delivery, and future needs. Results: Adolescent self‐harm is an important concern for senior management and teachers. However, emotional health and well‐being is the primary health priority for schools. Health services, such as Child and Adolescent Mental Health Services, and on‐site counselling are the main approaches schools currently use to address adolescent self‐harm, with counselling cited as the most useful provision. Fifty‐two per cent of schools have received some staff training on adolescent self‐harm, although only 22% rated the adequacy of this training as high. Where schools do not have existing provision, respondents stated that they would like staff training, specialist student training, external speakers, posters and assemblies, although the latter four options were infrequently ranked as the most useful approaches. Key barriers to addressing adolescent self‐harm were: lack of time in the curriculum; lack of resources; lack of staff training and time; and fear of encouraging self‐harm amongst adolescents. Conclusions: Adolescent self‐harm is a priority for schools. Intervention might focus on increasing the availability of training to teaching staff.